Animal Food Demand in Indonesian Rural: A Quadratic Almost Ideal Demand System Approach - Nikmatul Khoiriyah; Ratya Anindita; Nuhfil Hanani; Abdul Wahib Muhaimin (Sekolah Pascasarjana Universitas Brawijaya, 2019)
It is estimated that the protein consumption in Indonesia will increase up to 90 % in 2030. The objective of this study was to analyze the effect of price, income, and socio-demographic variables on demand for animal food in rural households in Indonesia. The demand estimation is using a Quadratic Almost Ideal Demand System. The research usedÂ Susenas 2016 data from 131,975 households. The results of the study confirmed that animal food is elastic, except the eggs. Beef is more sensitive to the household income changing. The increasing of household income increase beef and milk consumption. When the price of beef increases, the household consume the other protein resource (chicken, fish, and eggs) as substitutions. The increase of 1% beef price increase chicken, fish and milk consumption byÂ 0.17%, 0.13%, 0.05% respectively. The increase of income followed by milk price decreasing increase chicken and fish consumption by 0.14% and 0.04%. The increase of one person household member decrease consumption of egg, meat, and milk for 0.33%,Â 0.01%, and 0.05 %.